Effects of different sea bass-tilapia ratios on fish yield and the efficiency of sea bass as biological control of tilapia young in polyculture - Tesorero, Letecia Blacer (Graduate Faculty, University of the Philippines System, 1991)
Five triplicated treatments is in completely randomized design (CRD) representing the different sea bass-tilapia ratios of 1:15, 1:20, 1:25, 1:30, and 1:35 were evaluated in 15 units of 300 sq m ponds of the Iloilo State College of Fisheries, Barotac Nuevo, Iloilo. The earlier established sea bass-tilapia ratios and effects on fish yield of the same ratios butincreasing the stocking density of sea bass at 1,533 juveniles/ha were assessed. The stocking densities for tilapia were 23,000/ha ;30,666/ha ; 46,000/ha ; and 53,666/ha fro treatments I, II, III, IV, and V respectively. Average initial weight of the sea bass and tilapia ranged from 2.6 g to 27.1 g and 31.2 g to 38.3 g, respectively. Highest mean weights for sea bass and tilapia at harvest were obtained in treatment II (394.9 g and 123.1 g respectively). Mean weights of sea bass and tilapia for treatments I, III, IV, and V were 361.5 g and 120.6 g ; 352.5 g and 117.0 g ; 377.5 g and 117.4 g ; and 322.7 g and 114.3 g, respectively. The effects of treatments in mean weights of sea bass and tilapia at harvest were not significantly different (P>0.05). Sea bass survival did not differ significantly among treatments. Highest survival for both fish was obtained in treatment II, 80.4% (sea bass) and 94.3% (tilapia). On the basis of the results, best production for sea bass was obtained in treatment II which was not significantly different from treatment III. Survival and growth were highest in treatment II. In terms of combined total production however, treatment V recorded the highest (4,583.97 kg/ha) but only 7.3% sea bass was obtained. The percentage composition of tilapia that attained marketable size in treatments V and II were 92.7% and 87.8% respectively. This indicated the advantage of using 1:20 as the optimum ratio for sea bass and tilapia in polyculture.